Effect of Anti-Inflammatory and Antimicrobial Cosupplementations on Sepsis Prevention in Critically Ill Trauma Patients at High Risk for Sepsis - Kamel, Noha A.; Soliman, Moetaza M.; Abo-Zeid, Maha A.; Shaaban, Mona I. (Frontiers in Pharmacology, 2021)
Background Sepsis development in patients with trauma is associated with bad prognosis. This study investigated the effect of immunomodulatory interventions in major trauma patients at high risk for sepsis. Methods In a randomized, double-blinded, controlled design, severe trauma patients were stratified by leukocyte anti-sedimentation rate (LAR) test into high risk (HR) and low risk (LR) for sepsis. The HR patients were randomly allocated into intravenous vitamin C plus vitamin B1 (HR-CB), intramuscular vitamin D plus oral Lactobacillus probiotics (HR-DP) or control (HR-C) groups. The clinical trial was registered at clinicaltrials.gov (https://clinicaltrials.gov/show/NCT04216459). Outcomes The primary outcome was Acute Physiologic Assessment and Chronic Health Evaluation score II (APACHE II) score. Secondary outcomes included sepsis incidence, changes in Sequential Organ Failure Assessment (SOFA) score, and serum monocyte chemoattractant protein-1 (MCP-1) on day 6 from baseline, 28-day mortality, intensive care unit (ICU) and hospital discharge. Results The HR-DP, HR-CB and LR groups showed a significantly lower incidence of sepsis development (20%, 20% and 16%, respectively versus 60% in HR-C group, p-value=0.004). The three groups also showed a significant improvement in APACHE II and SOFA scores. Besides, MCP-1 levels were significantly decreased in HR-DP and HR-CB groups compared to HR-C group (p-value ≤ 0.05). Significantly decreased mortality (10% and 16% versus 60% in HR-C group) and increased ICU discharge (95% and 84% versus 45% in HR-C group) were observed in HR-CB and LR groups (p-value=0.001). Conclusion Both combinations of interventions improved APACHE II scores and reduced sepsis incidence in trauma patients. The LAR combined with injury severity score (ISS) were good sepsis predictors.